On a Couple of Nonlocal Singular Viscoelastic Equations with Damping and General Source Terms: Blow-Up of Solutions. (23rd August 2021) - Piskin, Erhan; Boulaaras, Salah Mahmoud; Kandemir, Hasan; Cherif, Bahri Belkacem; Biomy, Mohamed
Abstract : Under some given conditions, we prove the explosion result of the solution of the system of nonlocal singular viscoelastic with damping and source terms on general case. This current study is a general case of the previous work of Boulaaras.